2022
DOI: 10.3390/ijms23147510
|View full text |Cite
|
Sign up to set email alerts
|

A Cruciform Petal-like (ZIF-8) with Bactericidal Activity against Foodborne Gram-Positive Bacteria for Antibacterial Food Packaging

Abstract: Most antibacterial nanomaterials used in food packaging act by releasing reactive oxygen species (ROS), which cannot efficiently have an inhibitory effect by penetrating the cell wall of Gram-positive Staphylococcus aureus. In this work, we used the cruciform petal-like zeolite imidazole framework-8 (ZIF-8) synthesized in the water phase which can release active Zn compounds in aqueous solution and exert a stronger inhibitory effect on S. aureus. The experimental results demonstrated that the aqueous cruciform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…After 30 min coincubation in PBS, we found that the fluorescence intensity of DCFH dispersions was positively correlated to the concentration of the ZIF-8 suspension (Figure 2F), indicating that a higher concentration of ZIF-8 NPs tended to generate a higher concentration of ROS to kill bacteria more efficiently. 47 As the schematic diagram (Figure 2G) showed, the antibacterial mechanisms of Zn-ZIF-8 NPs may include induced ROS generation that leads to oxidative stress 9,47 and disrupted expression of intracellular nucleic acid, 48 electrostatic interaction between positively charged ZIF-8 NPs and negatively charged bacterial cells, 45,46 and damage to some liposomes by the release of imidazole rings. 49 Biocompatibility of ZIF-8 and DMOG@ZIF-8 In Vitro.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After 30 min coincubation in PBS, we found that the fluorescence intensity of DCFH dispersions was positively correlated to the concentration of the ZIF-8 suspension (Figure 2F), indicating that a higher concentration of ZIF-8 NPs tended to generate a higher concentration of ROS to kill bacteria more efficiently. 47 As the schematic diagram (Figure 2G) showed, the antibacterial mechanisms of Zn-ZIF-8 NPs may include induced ROS generation that leads to oxidative stress 9,47 and disrupted expression of intracellular nucleic acid, 48 electrostatic interaction between positively charged ZIF-8 NPs and negatively charged bacterial cells, 45,46 and damage to some liposomes by the release of imidazole rings. 49 Biocompatibility of ZIF-8 and DMOG@ZIF-8 In Vitro.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The good shelf life of the FeS 2 /CS@Gox system will also further improve its application in the detection of real samples. The nanozyme-based glucose-sensing system offers a good detection limit [ 43 ], and our system offers obvious benefits over other systems ( Table 1 ). In conclusion, the FeS 2 /CS@Gox system constructed by the immobilized enzyme strategy has excellent sensitivity, selectivity, and shelf life and is a potential product for glucose detection.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several approaches have been adopted to modify chitosan to achieve the desired food-packaging qualities. Incorporating different additives such as essential oils and plant extracts with chitosan significantly enhances the antibacterial and antioxidant properties, the current trend in a coating that improves the shelf life [ 11 , 12 , 13 , 14 ]. Additional modifications with starch, alginate, and pectin improve mechanical properties [ 15 ].…”
Section: Introductionmentioning
confidence: 99%